PENGEMBANGAN TEORI AKUNTANSI SYARIAH DI INDONESIA - Liza Septiyani; Trisna Afriyani; Gunawan Aji (Kampus Akademik Publiser, 2024)
Development of sharia accounting theory in Indonesia. The aim of this research is to determine the development of sharia accounting theory that already exists in Indonesia. The method used in this research is ex post facto analysis using urf as the main basis. This research found that sharia accounting theory ideally consists of rules that cover aspects of faith, ethical law and morality. Therefore, Islamic financial reports must have many tangible and intangible features. Thus, sharia accounting theory is used to support Allah's sharia both conceptually and practically.